Effect of Time Delay on Reperfusion After Tenecteplase in an Extended Time Window: Analysis From the CHABLIS‐T Trials - Lan Hong; Juehua Zhu; Zhijiao He; Xinru Wang; Siyuan Li; Xinyu Liu; Yifeng Ling; Lumeng Yang; Qi Fang; Qiang Dong; Xin Cheng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The association between time and reperfusion in an extended time window remains unexplored. This study aimed to investigate whether time delay was associated with reduced odds of reperfusion in patients with acute ischemic stroke treated with tenecteplase in the 4.5‐ to 24‐hour time window, in the CHABLIS‐T (Chinese Acute Tissue‐Based Imaging Selection for Lysis in Stroke‐Tenecteplase) trials. Methods Patients from the CHABLIS‐T and CHABLIS‐T II trials treated with tenecteplase were included. Major reperfusion was assessed via follow‐up perfusion imaging or digital subtraction angiography. Time intervals from symptom onset/last known well to hospital arrival/administration of tenecteplase were analyzed as continuous and categorical variables in multivariable logistic regression models. Subgroup analysis examined the consistency of the association across different patient characteristics. Results Sixty‐seven patients achieved postthrombolytic major reperfusion among the 199 patients included. Longer onset‐to‐arrival time was associated with lower odds of major reperfusion (continuous: odds ratio [OR], 0.98 per 10 minutes, P=0.004; categorical: OR, 0.45, P=0.003). Similarly, prolonged onset‐to‐thrombolysis time was associated with decreased probability of reperfusion (continuous variable: OR, 0.98 per 10 minutes, P=0.01; categorical variable: OR, 0.48, P=0.002). The analysis of time from last known well drew similar results. Subgroup analysis revealed that patients with nonatherosclerotic stroke were more susceptible to time delay. Conclusions Time delay was associated with reduced postthrombolytic reperfusion odds in patients with stroke treated with tenecteplase, especially in nonatherosclerotic cases. Prompt reperfusion remains essential, even in patients with benign perfusion profiles in an extended time window. Registration URL: https://clinicalTrials.gov; URL: CHABLIS‐T NCT04086147; CHABLIS‐T II NCT04516993